1999
DOI: 10.1046/j.1365-2168.1999.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing strategy for rectal cancer is associated with improved outcome

Abstract: These data are consistent with the interpretation that the results of treatment can be improved by concentration of surgery to a colorectal team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
10

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(69 citation statements)
references
References 17 publications
(7 reference statements)
5
54
0
10
Order By: Relevance
“…There has also been an increase in the use of preoperative radiotherapy (26), again with different starting points at different hospitals. Analyses have shown that survival for rectalcancer patients improved earlier in counties where the new treatments were first introduced (25). The better prognosis for rectal cancer compared with colon cancer observed during the most recent time periods is likely to be explained by improved treatment.…”
Section: Digestive Organsmentioning
confidence: 98%
See 1 more Smart Citation
“…There has also been an increase in the use of preoperative radiotherapy (26), again with different starting points at different hospitals. Analyses have shown that survival for rectalcancer patients improved earlier in counties where the new treatments were first introduced (25). The better prognosis for rectal cancer compared with colon cancer observed during the most recent time periods is likely to be explained by improved treatment.…”
Section: Digestive Organsmentioning
confidence: 98%
“…For rectal cancer, surgery has improved substantially. Total mesorectal excision was introduced in one Swedish county in 1986 (25) and has been performed at almost all hospitals undertaking rectalcancer surgery in Sweden since the mid-1990s. There has also been an increase in the use of preoperative radiotherapy (26), again with different starting points at different hospitals.…”
Section: Digestive Organsmentioning
confidence: 99%
“…The term 'total mesorectal excision' (TME) is often used for this type of surgery, although the entire mesorectum is not always excised in high rectal cancers. Concentration of rectal cancer surgery to a colorectal cancer unit and extensive surgical training programmes have also resulted in low local failure rates (approximately 10 Á/15% after 2 Á/5 years) in unselected Swedish patient populations (3,54) and in Norway (55). Several individual hospitals have also reported low recurrence rates after having introduced the TME concept (e.g.…”
Section: Radiotherapy In Resectable Rectal Cancermentioning
confidence: 99%
“…The recurrence rates among patients having had preoperative radiotherapy or surgery alone were 2% and 10%, respectively, indicating that radiotherapy affects the local recurrence rate, even if surgery is optimized (53). Data from Uppsala, Sweden revealed a recurrence rate of 3% when TME surgery was combined with preoperative radiotherapy (25 Gy in one week) (54).…”
Section: Is Adjuvant Radiotherapy Needed For the Treatment Of Rectal mentioning
confidence: 99%